Analisis Kesalahan Konsep Siswa dalam Menyelesaikan Soal pada Materi Perpangkatan - Julinsen D Banamtuan; Netty J M Gella; Urni Babys (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study is aimed to describe the students' errors in the concept of resolving the question about rank material with descriptive qualitative method. The subject of this study was 21 students at SMA Kisten Kapan in X MIPA A on the academic year 2020/2021. The instruments were test questions, interview sheets, and documentation. The data analysis result showed that concept errors were conducted by students on the rank material such as a). Students were not able to understand the symbol and place value; b). Students were erroneous in solving process; c). Misinterpreting the idea in writing systematically; d). Students Made the error mathematical model and formulate problems' strategies. The most dominant concept error Made by students was that students were not able to understand the symbol and place values because they were less careful in working on the questions. The teachers' role in overcoming these problems was to provide various activities in learning mathematics and provide varied practice questions that students learned independently.